2015
DOI: 10.1016/j.childyouth.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Permanence for disabled children and young people through foster care and adoption: A selective review of international literature

Abstract: This version is available at https://strathprints.strath.ac.uk/52269/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
9
1
1
Order By: Relevance
“…As for the childcare intervention process, in contrast with previous studies (Hill, 2012;Slayter & Springer, 2011;Welch et al, 2015), no significant differences in the number of changes of residential placements were found, although the results show a slightly higher mean number of changes in the group with ID. No differences in terms of the probability of having Águila-Otero et al…”
Section: Children With Intellectual Disabilitycontrasting
confidence: 99%
See 1 more Smart Citation
“…As for the childcare intervention process, in contrast with previous studies (Hill, 2012;Slayter & Springer, 2011;Welch et al, 2015), no significant differences in the number of changes of residential placements were found, although the results show a slightly higher mean number of changes in the group with ID. No differences in terms of the probability of having Águila-Otero et al…”
Section: Children With Intellectual Disabilitycontrasting
confidence: 99%
“…After entering the care system, children with ID remain longer than their peers without disability do and are subject to more changes of placement and programmes (Chmelka et al, 2011;Hill, 2012;Sainero, del Valle, López & Bravo, 2013;Slayter & Springer, 2011;Welch, Jones, Stalker, & Stewart, 2015). They have a 38-39% lower probability of returning to the family (Rosenberg & Robinson, 2004;Slayter, 2016) or of adoption (Baker, 2007), and when adopted, a higher probability of adoption breakdown (Slayter, 2016;Slayter & Springer, 2011).…”
Section: Children and Young People With Id In Carementioning
confidence: 99%
“…For this population, neglect due to lack of family conditions, deprivation of family power and family conflicts are more common. Furthermore, they are adopted less frequently and, therefore, many tend to grow old in foster care services 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In a review of literature, involving countries such as the United States, the United Kingdom, Canada, Australia, China and the Netherlands, Welch et al 24 observed that children and adolescents with disabilities and behavioral problems are less likely to achieve family reunification and stay longer in services, with a reduced probabil-ity of family reunification and adoption. Other studies from different parts of the world show similar results 12,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Experts (Welch, Jones, Stalker, & Stewart, 2015) have proved that older children and children with disabilities would be at risk in integrating and fostering belonging and bonding links with the adoptive family, experiences mostly insecurity and attachment problems. Although the presumption that adoption process is stressful for children is not recent, Brodzinsky, Smith, & Brodzinsky (1998) based his research on stress and coping theory and urges the need to understand the feelings that often can be ambivalent and confused (feelings of fear, anxiety, sorrow, regret, uncertainty etc.)…”
Section: General Recommendations For Adoption Of Hardly Adopted Childrenmentioning
confidence: 99%